Implementation of Decision-Making Algorithms and Key Requirement Approach for Vendor Selection in Telecommunication Device Bidding - Patria Adhistian; Dyah Puspitasari Sunaryo Putri; Ihsan Supono; Priyo Wibowo (Jurnal Rekayasa Sistem & Industri, 2023)
The influence of perceived quality is a classic problem in a vendor selection process. To overcome thisproblem, many algorithms have been used in decision making. In this paper we have carried out theidentification of planning team needs and the optimization of the bidding scheme using key requirements tominimize the influence of quality perceptions. The Kano Model Analysis method, the Analytical HierarchyProcess and Technique for Order Preference by Similarity to the Ideal Solution are used to analyze anddetermine the key requirements in the bidding process for telecommunications equipment needed by theplanning team. Vendor selection based on key of requirements specifications is carried out in six stages,namely the preparation stage, requirements search, selection of Key of Requirements specifications, vendorselection, accuracy testing and conclusions. The results of the analysis show that the need for new planningand architecture of telecommunication service providers can increase to NFVi and services. An importantcriterion for NVFi (Hardware) development is Virtual Infrastructure Management (VIM) with a weight of22%, while the service criteria are Fixed Services with a weight of 50.94%. Based on the analy